Elucidating the Changes in Activated Carbon Pore Structure as a Result of -Butylbenzene Adsorption and its Desorption by Means of Supercritical Carbon Dioxide - Henryk Grajek (Adsorption Science & Technology)
Inverse gas chromatography was applied to characterize the changes in pore structure of activated carbon samples (commercial, de-ashed, and de-ashed and oxidized) before and after the adsorption of tert -butylbenzene, and after its desorption by means of supercritical carbon dioxide. The slit-like micropore model was used for the description of the pore structure. It was shown that tert -butylbenzene was desorbed with greater difficulty from samples containing basic impurities. Changes in the amounts of surface groups (acidic and basic) during the desorption process were not significant.